Application of Waste Tire Carbon for Iron-Containing Dust Reduction in Industrial Processes - Menglan Zeng; Chujun Luan; Fawei Lin (Applied Sciences)
The iron and steel industry generates large quantities of iron-bearing dust (IBD), contributing to resource inefficiency and environmental concerns. This study investigates heating methods and the use of organic solid waste, specifically waste tire carbon (WTC), as a reductant for the recovery of Fe from sintering machine tail dust (SMTD) and steelmaking gravity dust. The results indicate that the optimal reduction conditions occurred at 1000 °C, with a 2:1 ratio of SMTD to WTC, and 0% O2 holding for 45 min. WTC is the best material, and heating methods affect it limitedly. The leaching behavior of seven metals was measured, showing an increase in the leaching of Ca and Al compared to the raw materials. The study shows that WTC provides a promising alternative reductant for IBD reduction, offering an energy-saving and low-carbon alternative to conventional fossil fuel injections in blast furnaces. The risk of Cr leaching should be paid attention to while enhancing Fe recovery.